Analisis Yuridis Perlindungan Konsumen terhadap Praktik Pinjaman Online Ilegal di Indonesia - Yogi Tri Cahyo; Hasanuddin Hasim (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of information technology has encouraged the emergence of online lending services as part of digital financial innovation. While these services provide easier access to financing, the proliferation of illegal online lending platforms has created various problems, including unlicensed operations, unreasonable interest rates, misuse of personal data, and debt collection practices involving threats and intimidation. This situation highlights the importance of legal protection for the public as consumers. This study aims to analyze legal protection for victims of illegal online lending, the obstacles to law enforcement, and the solutions to address these issues. The research employs a normative juridical method using statutory, conceptual, and case approaches through a literature review. The findings indicate that Indonesia has established regulations concerning consumer protection, electronic transactions, personal data protection, and the supervision of digital financial services. However, their implementation remains suboptimal due to weak regulatory oversight, low public literacy, and the rapid evolution of illegal online lending schemes. These practices also contradict the principles of legal certainty, justice, and balance. The study concludes that efforts to combat illegal online lending should be carried out through preventive measures, such as public education and expanding access to legitimate financing services, as well as repressive measures through firm law enforcement against perpetrators.